The Implementation of Blended Learning Based on MOODLE on Student’s Chemistry Learning Outcome at Class X in SMA Negeri 3 Poso - Wayan A. K. Mahardika; Vanny M. A. Tiwow; Suherman Suherman (Jurnal Akademika Kimia, 2019)
The growth of technology has encouraged learning toward blended learning which combines e-learning-based learning with the conventional face-to-face learning system. The use of MOODLE software to created web-based virtual class and the benefits of social interaction, making blended learning to has a more flexible and efficient time with more varied learning media. This research aimed to determine the effect of the implementation of blended learning based on MOODLE on student chemistry learning outcomes at class X in SMA Negeri 3 Poso. The research was conducted by giving treatment to the experiment class 1 (n = 32) and repeating the same treatment to the experiment class 2 (n = 33). The average pretest value in experiment class 1 was 19.06 and in experiment class 2 was 20.30. While the average of posttest value in experiment class 1 was 76.50 and in experiment class 2 was 73.00. The test of hypotheses was conducted using the Wilcoxon Signed Rank Test with criteria is, if –Ztable ≤ Zcalculate ≤ +Ztable then H0 is accepted. The value of Zcalculate in experiment class 1 was -4.93 and in experiment class 2 was -5.01. Based on the data, it been concluded that there was an effect of the implementation of blended learning based on MOODLE on student’s chemistry learning outcomes at class X in SMA Negeri 3 Poso.